Environment and Happiness : Valuation of Air Pollution in Ten European Countries - Heinz Welsch (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
This paper uses a set of panel data from happiness surveys, jointly with data on per capita income and pollution, to examine how self-reported well-being varies with prosperity and environmental conditions. This approach permits to show that citizens care about prosperity and the environment, and to calculate the trade-off people are willing to make between them. The paper finds that air pollution plays a statistically significant role as a predictor of intercountry and inter-temporal differences in subjective well-being. The effect of air pollution on well-being shows up as a considerable monetary valuation of improved air quality. The air quality improvements achieved in Western Europe in 1990-1997 are valued at almost 900 per capita per year in the case of nitrogen dioxide and more than 1400 per capita per year in the case of lead.
Keywords: Q2; 330; pollution; environmental valuation; subjective well-being; marginal rate of substitution; Luftverunreinigung; Luftreinhaltung; Lebensstandard; Lebensqualitaet; Schaetzung; Westeuropa; Lebenszufriedenheit